CSF and Plasma Cholinergic Markers in Patients With Cognitive Impairment - Karami, Azadeh; Darreh-Shori, Taher; Schultzberg, Marianne; Eriksdotter, Maria (Frontiers in Aging Neuroscience, 2021)
Introduction: Alzheimer’s disease (AD) is the most prevalent form of dementia with symptoms of deteriorating cognitive functions and memory loss, partially as a result of a decrease in cholinergic neurotransmission. The disease is incurable and treatment with cholinesterase inhibitors (ChEI) is symptomatic. Choline acetyltransferase (ChAT), the enzyme that synthesizes acetylcholine (ACh), has been proven recently to be present in both cerebrospinal fluid (CSF) and plasma. As ChAT plays a role in regulating the extracellular ACh levels, it may have an impact on prognosis and cognitive performance in AD patients. Objectives: To measure ChAT activity and its protein concentration in CSF and plasma from patients with AD, mild cognitive impairment (MCI) or Subjective cognitive impairment (SCI). Methods: Plasma and CSF samples were obtained from 21 AD, 32 MCI and 30 SCI patients. The activity and protein levels of ChAT and acetylcholine esterase (AChE), the enzyme catalyzing the hydrolysis of ACh, were analyzed using an integrated activity and protein concentration ELISA-like assay. A Cholinergic Index was calculated as the ratio of ChAT to AChE activities in CSF. The data were analyzed in relation to dementia biomarkers and cognitive performance of the patients. Results: The CSF ChAT activity was significantly higher (55-67%) in MCI patients compared to AD and SCI cases. The CSF Cholinergic Index was 41% and 22% lower in AD patients than in MCI and SCI subjects, respectively. This index correlated positively with the Aβ42/p-tau ratio in CSF in SCI but negatively with that in AD and MCI. The ChAT activity and protein levels in plasma exhibited significant differences with the pattern of AD>>MCI>SCI. Conclusions: This is the first study investigating soluble levels of the key cholinergic enzyme, ChAT, in both plasma and CSF of individuals at different clinical stage of dementia. Although further validation is needed, the overall pattern of the results suggests that in the continuum of AD, the cholinergic signaling exhibits an inverse U-shape dynamic of changes in the brain that greatly differs from the changes observed in the plasma compartment.